Cultural influences moderating learners’ adoption of serious 3D games for managerial learning - Siala, Haytham; Kutsch, Elmar; Jagger, Suzy (Elsevier, 2019)
Purpose The purpose of this paper is to investigate whether learners from different cultures adopt a serious 3D game to facilitate the learning of transferable managerial skills (ethics) and knowledge. Design/methodology/approach A cross-sectional, cross-country survey study (n=319) was conducted recruiting participants from one North American and two British universities. The survey data and the conceptual model have been analysed and tested using confirmatory factor analysis and structural equation modelling. Findings Participants displayed positive attitudes towards the 3D game and responded positively to theory presented as “real-life” scenarios; gamification techniques such as interactions and dialogue, and rewards and progression levels, which are part of the game, albeit the participants’ adoption was driven more by extrinsic motivations (rewards) than intrinsic ones (ease of use and entertainment). In addition, the empirical results suggest that when gender is taken into account, the perceptions and needs of cross-cultural learners in serious gaming environments vary and display characteristics that are similar to Rogers’ five adopter categories; thus, culture could significantly shape learners’ decisions to adopt a serious game as a managerial learning tool. Research limitations/implications For future researchers, this paper highlights various levels of training, support and promotional awareness that need to be considered to facilitate the adoption of serious games for managerial learning. Practical implications For academics and practitioners in work-based learning and managerial training environments, this paper highlights the salient factors that need to be inherent in a serious 3D game, and best practices for scaffolding existing instructional approaches or training interventions. Originality/value In light of Rogers’ five adopter categories, this cross-country study involving culturally diverse learners provides key insight into the potential application of serious games as a practice-based learning instrument in academia and industry.
Keywords: Blended learning; Technology adoption; Serious games; Practice-based learning; Adoption theory; Cross-cultural issue; Technology-mediated andragogy